Splitting the multiphase point - Yeomans, J (1996)
Models with competing interactions, for example the ANNNI model, can have special points at which the ground state is infinitely degenerate, so-called multiphase points. Small perturbations can lift this degeneracy and give rise to infinite sequences of long-period phases. This paper compares the effect of three possible perturbations, quantum fluctuations, thermal fluctuations and the softening of the spins from their quantised positions.